Public-public partnerships - Škof, Bojan (Lex localis, 2010)
Despite the clearly specified conditions laid down in the Slovenian local self-government act, both in theory and practice, the questions often arises whether or not the Slovene municipalities are able to perform original tasks. In this regard, it must be noted that the local communities, i.e. municipalities and wider self-governing local communities, are not formed on the basis of certain criteria of rationality according to which it would be possible to prejudge whether or not they are capable of performing the tasks that they must perform, namely, the local public services. Today's municipalities are mostly the result of the historical development, traditions, political compromises, geographical and other factors that have nothing to do with the criteria of rationality with regard to the tasks and needs they must carry out and satisfy. Due to a large number of relatively weak local communities in Slovenia, the cooperation between them is important in carrying out the functions that are common to municipalities, to the state or to the EU. It is about publi-public partnerships where local communities can play a key role because they know the needs of the local population.
Keywords: lokalna samouprava; lokalne oblasti; občine; Slovenija; sodelovanje